2004
DOI: 10.2174/0929867043363820
|View full text |Cite
|
Sign up to set email alerts
|

Dendrotoxins: Structure-Activity Relationships and Effects on Potassium Ion Channels

Abstract: Dendrotoxins are small proteins isolated from mamba (Dendroaspis) snakes. The original dendrotoxin was found in venom of the Eastern green mamba, Dendroaspis angusticeps, and related proteins were subsequently found in other mamba venoms. The dendrotoxins contain 57-60 amino acid residues cross-linked by three disulphide bridges, and they are homologous to Kunitz-type serine protease inhibitors, such as aprotinin (BPTI). The dendrotoxins have little or no anti-protease activity, but they block particular subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 0 publications
0
101
0
4
Order By: Relevance
“…The effects of DTx-K, a related polypeptide that selectively blocks Kv1.1-containing channels (Harvey and Robertson, 2004) on the cold threshold, were nearly identical to those observed with ␣-DTx. On average, 1 M DTx-K shifted the threshold by 3.5 Ϯ 0.8°C (n ϭ 19) (supplemental Table 1, available at www.jneurosci.org as supplemental material).…”
Section: Kv1 Channels Are the Molecular Counterparts Of I Kd In Cold-mentioning
confidence: 66%
See 2 more Smart Citations
“…The effects of DTx-K, a related polypeptide that selectively blocks Kv1.1-containing channels (Harvey and Robertson, 2004) on the cold threshold, were nearly identical to those observed with ␣-DTx. On average, 1 M DTx-K shifted the threshold by 3.5 Ϯ 0.8°C (n ϭ 19) (supplemental Table 1, available at www.jneurosci.org as supplemental material).…”
Section: Kv1 Channels Are the Molecular Counterparts Of I Kd In Cold-mentioning
confidence: 66%
“…The blocking actions of DTx-K and tityustoxin-K␣ indicate that Kv1.1 and Kv1.2 are part of the channel complex forming I KD (Wang et al, 1999;Harvey and Robertson, 2004) and excludes homomeric Kv1.2 channels, which are insensitive to DTx-K. Intriguingly, Kv1.1 knock-out mice show prominent cold-induced discharges in myelinated motor nerves (Zhou et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously determined dose-response relationships for the blockers, and we chose doses that were specific for the relevant subunits (Guan et al 2006(Guan et al , 2007b. To study putative Kv1-mediated current (Guan et al 2006), we applied 100 nM ␣-dendrotoxin (DTX, blocks current through channels containing Kv1.1, Kv1.2, or Kv1.6 subunits; Harvey and Robertson 2004) and 10 -30 nM margatoxin (MTX, blocks Kv1.3-containing channels; Garcia-Calvo et al 1993). The putative Kv1-mediated current was defined as the difference between currents recorded in control solution and currents in the presence of DTX plus MTX.…”
Section: Current Isolationmentioning
confidence: 99%
“…It has been suggested that toxins evolved from endogenous genes that function in normal cellular pathways (3,4). Indeed, venomous creatures possess toxins with homology to several proteins, including acetylcholinesterases (5), phospholipases (6,7), nerve growth factor (8), endothelins (9), Lynx-1 (10,11), Kunitz-type serine protease inhibitors (12), and the ion channel regulatory (ICR) 5 domains of cysteinerich secretory proteins (CRISPs) (3,13,14). Mammalian proteins containing toxin-like domains (TxDs) that block K ϩ channels have not been characterized previously.…”
mentioning
confidence: 99%